Genetic Variation Analysis of L1 gene HPV-16 using RFLP in Silico - Afionita, Santi; Putri, Dwi Hilda; Achyar, Afifatul; Yuniarti, Elsa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Human papillomavirus (HPV) is one of the leading causes of cervical cancer, with the L1 gene playing an important role in vaccine development. This study aims to analyze the genetic variation of the L1 gene of HPV types 16, 18, 52, and 58 using the RFLP method in silico by utilizing restriction enzymes. The results showed that. The pattern of genetic conservation is more dominant in HPV 16 and 52 than other types, indicating the potential important role of the L1 gene in vaccine development. This study confirms the importance of analyzing genetic variation to understand HPV genetic diversity. These results may contribute to the development of more specific vaccines and molecular markers for HPV detection.